"Otroški bidermajer" na Slovenskem - Kobe, Marjana (Primerjalna književnost, 2001)
"Children's Biedermeier" in Slovenia. This article deals with the reception of Christoph Schmid's prosodic pattern for children, which was the first to introduce children's Biedermeier (Sengle) to Slovenia. Through a typological and morphological analysis and an analysis of motifs and themes in imitations of Schmid's matrix in the first Slovene youth newspaper, Vedež (1848-1850), the author shows that children's Biedermeier was introduced to Slovenia via youth literature in the 19th century in its pure form, so to speak, although with a delay.
Keywords: children's literature; otroška književnost; 19.st.; literarne študije; bidermajer